Following the steps of CHIPA: Chilenia and Patagonia formed the same drift terrain that collided with the southwest Gondwana margin during the middle Paleozoic - Tomezzoli, Renata Nela; Cristallini, Ernesto O.; Tickyj, Hugo; Arzadún, Guadalupe; Calvagno, Juan Martín; Choque, Giselle; Febbo, Belen; Saguas, Eliana (Frontiers in Earth Science, 2023)
Geological evidence indicates that the deformation along the southwest Gondwana margin began during the Middle-to-Late Devonian (the Acadian-Cháñica orogenic phase in Argentina). It has been interpreted that this deformation occurred as a consequence of the collision of Chilenia from the west and Patagonia from the south-southwest with Gondwana. As both Chilenia and Patagonia collided at the same time, in this study, we proposed that these continental blocks conform to the same allochthonous drift terrain, named here as CHIPA. The geological evolution of this margin is still under debate. Field work, paleomagnetic studies, and anisotropy of magnetic susceptibility (AMS) studies were integrated from different localities along this paleomargin in Argentina. In Permian rocks, all the geological indicators show a clear regional NW-SE elongation signature and NE-SW shortening direction. The middle Devonian to Permian patterns are more complex as the result of stress interference and the overlapping of orogenic activities with different intensities and ages. The deformation that started as the product of the CHIPA collision with Gondwana during the Middle Devonian continued through the Permian (the Hercinian-San Rafael orogenic phase in Argentina) as post-collisional compressive deformation, consequence of the paleogeographic re-organization of Gondwana and Laurentia, which moved toward the Equator from the south and the north, respectively, to form the Pangea supercontinent during the Triassic.